Tantangan Perempuan Karir pada Kepala Madrasah Raudhatul Athfal di Kemetrian Agama Kabupaten Maros - Rezki Nurfyanti; A. Octamaya Tenri Awaru; M. Ridwan Said Ahmad; Ashari Ashari; Najamuddin Najamuddin (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to identify and analyze the challenges faced by career women serving as Heads of Raudhatul Athfal (RA), or early childhood Islamic education institutions. In their roles, female school leaders are expected not only to manage the institution professionally but also to balance family responsibilities and personal life. The findings reveal several key challenges, including emotional strain such as frequent anger and sudden crying, time-consuming administrative tasks like school accreditation, limited quality time with family, curriculum changes, miscommunication with parents, differences in students' personalities, conflicts with colleagues, and often-neglected health issues. These challenges are interconnected and can affect leadership effectiveness and overall school management quality. The study suggests the importance of emotional support, stress management training, improved interpersonal communication skills, and institutional policies that are more accommodating to the needs of female school leaders. With the right strategies, these challenges can be addressed, allowing headteachers to perform their roles effectively and sustainably.